Nitric oxide and glucocorticoids synergize in inducing apoptosis of CD4+8+ thymocytes: implications for ‘Death by Neglect’ and T-cell function - Cohen, Orly; Herr, Ingrid (International immunology, 2012)
Abstract. Thymic epithelial cells (TECs) play a central role in T-cell development by presenting self-antigens on MHC proteins. Double-positive (DP) thymocytes